Effect of Cost-Sharing Federal Programs on Adoption of Water Conservation Practices: Results from Propensity Score Matching Approach - Adusumilli, Naveen; Dikitanan, Rowell; Wang, Hua (World Scientific Publishing, 2020)
The extent of recommended conservation practices is crucial for addressing natural resource concerns on the farms. The practices implementation is supported by working lands conservation programs, the Environmental Quality Incentives Program and the Conservation Stewardship Program. The paper applies a propensity score matching approach to evaluate the effects of enrollment in the two federal conservation programs on irrigation water conservation practices adoption in Louisiana row crop agriculture. The analysis reveals that enrollment in the programs leads to statistically significant greater adoption of water management practices. The analysis provides correction for selection bias in adoption that can result from not accounting for the differences between program participants and non-participants. The analysis enables to provide a stronger and relatively accurate argument about the impact of conservation support programs on the adoption of conservation on the ground.